Dissecting the hack the v3rb0ten network - Street, Jayson E.; Sims, Kristin; Baskin, Brian (Syngress is an imprint of Elsevier, 2015)
Dissecting the Hack: The V3rb0t3n Network ventures further into cutting-edge techniques and methods than its predecessor, Dissecting the Hack: The F0rb1dd3n Network. It forgoes the basics and delves straight into the action, as our heroes are chased around the world in a global race against the clock. The danger they face will forever reshape their lives and the price they pay for their actions will not only affect themselves, but could possibly shake the foundations of an entire nation. The book is divided into two parts. The first part, entitled ""The V3rb0t3n Network, "" continues the fic